Risk Factors and Seroprevalence of Hepatitis C among Patients Hospitalized at Mulago Hospital, Uganda. (9th August 2011) - O'Reilly, J. I.; Ocama, P.; Opio, C. K.; Alfred, A.; Paintsil, E.; Seremba, E.; Sofair, A. N.
Abstract : The emergence of hepatitis C virus (HCV) and its associated sequelae in Africa is a cause for significant concern. Human immunodeficiency virus (HIV) positive patients are at an increased risk of contracting HCV infection due to similar risk factors and modes of transmission. We investigated the seroprevalence of hepatitis C in hospitalized HIV-positive and HIV-negative patients in Mulago Hospital, an academic hospital in Uganda. Blood samples were first tested for HCV antibodies, and positive tests were confirmed with HCV RNA PCR. We enrolled five hundred patients, half HIV-positive and half HIV negative. Overall, 13/500 patients (2.6%) tested positive for HCV antibodies. There was no difference in HCV antibody detection among HIV-positive and HIV-negative patients. Out of all risk factors examined, only an age greater than 50 years was associated with HCV infection. Traditional risk factors for concurrent HIV and HCV transmission, such as intravenous drug use, were exceedingly rare in Uganda. Only 3 of 13 patients with detectable HCV antibodies were confirmed by HCV RNA detection. This result concurs with recent studies noting poor performance of HCV antibody testing when using African sera. These tests should be validated in the local population before implementation.